The Direction of Islamic Education Transformation from the Perspective of Millennial Teachers - Moh Rixa Setiawan; Andi Anirah; Nasrul Nasrul (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The development of the Industrial Revolution 4.0 and the acceleration of digital transformation have brought significant changes to the educational landscape, including Islamic education, which faces the challenge of maintaining the authenticity of spiritual values ​​while meeting the demands of 21st-century competencies. In this context, the role of millennial teachers is crucial as a generation that grew up in a digital ecosystem and has the potential to be agents of pedagogical and epistemological change. However, previous studies have tended to focus on structural and administrative aspects, without in-depth examination of the role of millennial teachers in guiding the paradigmatic transformation of Islamic education. This study aims to analyze the direction of Islamic education transformation from the perspective of millennial teachers by highlighting three main dimensions: scientific and value paradigms, pedagogical strategies, and implementation challenges in the digital era. The study employed a qualitative case study design at SMPN 1 Sarjo. The study subjects comprised the madrasah principal and six millennial teachers, selected purposively. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model with triangulation techniques to ensure validity. The research findings demonstrate a paradigm shift from dogmatic learning to a reflective, dialogical, and contextual model, accompanied by the integration of technology as a pedagogical medium and educational da’wah, still grounded in Islamic digital ethics. This transformation has led to increased student participation and a deeper understanding of practical applications. The implications of this research emphasize the importance of strengthening teachers’ digital and pedagogical competencies and systemic policy support to realize a hybrid, adaptive, and integrated Islamic education model in the digital era.